Criminalization failure security of persons taken under protection - Будім, Іван Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The aim of the article is the analysis of the conditions of criminalization and the development of legislation on criminal liability for failure to take precautions against persons taken under protection. The norms, providing for responsibility for the attack on the judiciary and the parties involved to engage in criminal proceedings and for failing to take security measures against such persons (from the times of Kievan Rus to the present).